The Ethicist Conception of Environmental Problems. (1st May 2000) - Dickson, B.
Abstract : Ethicist assumptions about the causes and solutions of environmental problems are widely held within environmental philosophy. It is typically assumed that an important cause of problems are the attitudes towards the natural environment held by individuals and that problems can be solved by getting people to adopt a more ethical orientation towards the environment. This article analyses and criticises these claims. Both the highly mediated nature of the relationship between individuals and the natural environment and the pervasive pressure on firms in market economies to reduce their costs provide reasons to question the ethicist assumptions.